2015
DOI: 10.5604/12321966.1196878
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, antioxidant vitamins and lipids as biomarkers of neurodegeneration in Alzheimer’s disease versus non-Alzheimer’s dementia

Abstract: Introduction and objective. Evidence for the benefit of antioxidants' based therapeutic intervention in dementia are inconsistent. Parallel studies in disease forms of dementia different than Alzheimer's are even less conclusive. In this study, the role of serum levels of homocysteine (tHcy), lipids and antioxidants in predicting the risk of cognitive decline in Alzheimer's disease (AD) versus non-Alzheimer's dementias (n-AD). The objective was to add to the ongoing cumulative research to establish the biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…Hypovitaminosis is implicated in the pathogenesis of various disorders [ 334 , 335 ], and there is increasing evidence that vitamins also play a key role in neurodegenerative diseases, leading to hypotheses concerning their use as disease biomarkers [ 336 , 337 ]. Regarding AD, although preliminary data are certainly encouraging, and the role of vitamins as biomarkers for AD has been widely investigated in literature ( Table 3 ) [ 188 , 297 , 338 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 , 350 , 351 ], some limitations in terms of consistency, reproducibility, and specificity remain to be solved, and further research is needed before hypothesizing a clinical application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypovitaminosis is implicated in the pathogenesis of various disorders [ 334 , 335 ], and there is increasing evidence that vitamins also play a key role in neurodegenerative diseases, leading to hypotheses concerning their use as disease biomarkers [ 336 , 337 ]. Regarding AD, although preliminary data are certainly encouraging, and the role of vitamins as biomarkers for AD has been widely investigated in literature ( Table 3 ) [ 188 , 297 , 338 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 , 350 , 351 ], some limitations in terms of consistency, reproducibility, and specificity remain to be solved, and further research is needed before hypothesizing a clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding vitamins A and E, while data from a cross-sectional study reported decreased blood concentrations of vitamin A in AD participants [ 351 ], in another study, serum deficiency of both vitamin A and E was correlated with cognitive impairment in patients with dementia other than Alzheimer’s [ 350 ], thus emphasizing that additional studies are required to better assess both the specificity and consistency of these potential biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, an imbalance of this metabolic pathway, marked by hyperhomocysteinemia and/or an altered SAM/SAH ratio, is a hallmark of memory loss and cognitive decline in elderly populations [34, 35] This loss of metabolic homeostasis may result from deficiency in metabolites and co-factors—such as vitamin B 12 or folic acid—directly and indirectly involved in the methylation of homocysteine. An increased interest exists to decipher their role as potential biomarkers of neurodegeneration in Alzheimer’s disease [3638]. The robustness of our method for the sensitive detection and quantitation of the 17 metabolites and co-factors of methionine metabolism was assessed in biological materials collected from healthy donors and patients diagnosed with Alzheimer’s disease.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 121 additional papers failed to meet the inclusion criteria. Therefore, this selection resulted in 17 studies [5][6][7][8][13][14][15][16][17][18][19][20][21][22][23][24][25] that were identified to have as met the rigid inclusion criteria (Figure 1). Table 1 shows the basic characteristics of the selected studies included in this meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%